Some account of the hamlet of East Burnham : (Savill & Edwards, 1858)
A late resident is Harriet Grote. - For private circulation. - Pasted in : Stanzas on Felix Mendelssohn : written in Burnham Beeches, January 1848 / [by H.G.?] In : Notice of the life of Thomas Moore. Spine title : Madam Grote, Ménages.